HUBUNGAN KOMPOSISI TUBUH DAN STATUS GIZI DENGAN PERKEMBANGAN SEKSUAL PADA REMAJA PUTRI DI PERKOTAAN DAN PERDESAAN - Mega Seasty Handayani; Cesilia Meti Dwiriani; Hadi Riyadi (Food and Nutrition Society of Indonesia, 2013)
The objective of this study was to analyzed the association of percent body fat and nutritional status on sexual development in adolescence girls in urban and rural areas. A cross sectional study involved 100 students of 8th grade junior high school. Age of menarche and breast growth used as sexual development indicators. Results showed that proportion of subjects with stunting and severe stunting was higher in rural area (34%) than urban area (14%). Subjects in urban area had earlier age of menarche (18%). Breast growth of subjects in urban and rural areas were in midpuberty phase. Statistical analysis showed a correlation between nutritional status (BMI/U) and percent body fat, nutritional status and sexual development, as well as percent body fat and sexual development (p<0.05).